Biodiversity and coarse woody debris in southern forests : proceedings of the Workshop on Coarse Woody Debris in Southern Forests: Effects on Biodiversity, Athens, GA, October 18-20, 1993 / editors, James W. McMinn and D.A. Crossley, Jr. (1996)
Summary goes here